Confirmation test of suspected Mycobacterium avium subspecies paratuberculosis (MAP) isolated using PCR F57 - Widagdo Sri Nugroho; Rahmat Setya Adji; Aeth Wahyuni (Jurnal Ilmu Ternak dan Veteriner, 2008)
Seropositive and isolate suspected as Mycobacterium avium subspecies paratuberculosis (MAP) was detected at dairy cows in West Java. This bacteria causes Johne’s disease (JD) and potentially becomes a new emerging disease for Indonesian dairy cows. The aim of this study was to confirm the suspected local isolate as a MAP distinctively by PCR. Reculture of MAP reference isolate, suspected local isolate done by resuspending bacteria in PBS 0.5% and inoculating it in Herrold’s egg yolk medium with mycobactin J (HEYM) and than inoculating it in 37oC for 16 weeks. The cultures grew in various time, Mycobacterium avium subspecies avium was detected in 3rd week, MAP reference was detected in 7th week, and local isolate was detected in 14th week. The confirmation test was carried out by PCR with primer F57. The PCR F57 result showed that MAP suspected isolate was not a Mycobacterium avium subspecies paratuberculosis. Key Words: Local Isolate, Mycobacterium avium Subspecies Paratuberulosis, PCR F57